A framework for collaborative supply chain: Level 1 - planning for redesign - Mohamed Udin, Zulkifli; Khan, M.K. (2002)
In improving the competitiveness of business organisations in the 21” century, minimizing cost and increasing productivity are no longer factors that can promise success.The changes in customer trends which are focusing more on product or service customization, high quality and short delivery times are additional crucial factors that organisations should be aware of: These factors have direct impact on how the management can make a decision in utilizing the capability of its Supply Chain Management (SCM). The intention of the paper is to promote the utilization of a Knowledge-Based System (KBS) in identifying organisations current position and evaluate the business process of an existing SCM in order to shift its environment and focus to become collaborative SCM. A model for collaborative SCM is currently being developed by the authors and will be used in the next stage of the research.